Undian Berhadiah Alfamart di Kota Bengkulu dalam Perspektif Ekonomi Syariah - Wahyu Abdul Jafar (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
This study aims to examine the issue of lucky draw that has been held by the management of Alfamart in the city of Bengkulu for the marketing interests of a produk. In order to reap maximum profits from consumers, the management of Alfamart in City of Bengkulu did not hesitate to give gifts to lucky consumers. But the problem is, sometimes this lucky draw still contains gambling (Maisyir). This research is included in the field research category, while in analyzing the data obtained, researchers use normative approaches. Data collection techniques used are interview techniques and documentation. After an in-depth study obtained a conclusion that law of the Alfamart lucky draw in the city of Bengkulu is divided into two, namely: First, the law is halal if the lucky draw is made into prizes without financial requirements to buy certain products or pay a certain amount of money. This gift is purely a form of ta'dhiman (Respect) or Mahabah (affection). The second, the law is haram, if the lucky draw uses a lottery system or gambling, that is, someone can take part in the lucky draw if you have purchased a certain produk or after paying money with a certain amount of money.